Dynamics of knowledge, skills and abilities in the process of personal physical education based university students - S.I. Belykh (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
The directions of development of physical culture of the students were considered. The presence of the knowledge and skills of the students in the field of physical culture is shown. The conditions for self-regulation of mental and physical condition of the person. In the experiment involved 640 students (boys, n = 320 and girls, n = 320). Applied research profile degree of development of athletic activities. Show the direction of the implementation of individually oriented physical education. Found that students' knowledge correspond to the first level (deep and full of knowledge and skills needed to use them) and the second (the presence of diverse, but not full knowledge). Formed skills that relate to perform common exercise. Recommended directions for the formation of skills that are needed for fitness activities.